Singly generatedC *-algebras - Rabanovych, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider a C*-algebra A generated by k self-adjoint elements. We prove that, for n k - 1 , the algebra M_n (A) is singly generated, i.e., generated by one non-self-adjoint element. We present an example of algebraA for which the property that M_n (A) is singly generated implies the relation n k - 1.